Rehabilitation of degraded areas in northeastern Patagonia, Argentina: Effects of environmental conditions and plant functional traits on performance of native woody species - Zeberio, Juan Manuel (2020)
Fil: Zeberio, Juan Manuel. Universidad Nacional de Río Negro. Centro de Estudios Ambientales desde la Norpatagonia (CEANPa). Río Negro, Argentina.